2017
DOI: 10.16930/rccc.v16n49.2401
|View full text |Cite
|
Sign up to set email alerts
|

Nível de disclosure nos relatórios de sustentabilidade em conformidade com o Global Reporting Initiative (GRI)

Abstract: RESUMOO objetivo do artigo é analisar o nível de disclosure nos relatórios de sustentabilidade em conformidade com o Global Reporting Initiative (GRI) nas empresas listadas na BM&FBovespa. Nesse sentido, realizou-se pesquisa descritiva com procedimentos de coleta documental e abordagem quantitativa. A amostra analisada ficou composta por 93 empresas listadas na BM&FBovespa, que divulgaram o relatório de sustentabilidade no ano de 2014 em conformidade com o modelo GRI. Os resultados mostram que à medida em que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(11 reference statements)
1
3
0
8
Order By: Relevance
“…While Table 6 shows the mean scores of each sector, the Communication Services segment is highlighted as the sector with the highest technical efficiency on average (46.86%), according to the multidimensional performance indicators and the methodology adopted in this study. The results are in line with the studies by Degenhart et al (2016) and Di Domenico et al (2017), which reveal public utility companies as the ones that highlight environmental information the most. In this study, this sector had in the second best position regarding technical efficiency, with a score of 44.37%, allowing to infer that this segment has a higher adjustment in ESG variables.…”
Section: General and Sectoral Rankingsupporting
confidence: 90%
See 1 more Smart Citation
“…While Table 6 shows the mean scores of each sector, the Communication Services segment is highlighted as the sector with the highest technical efficiency on average (46.86%), according to the multidimensional performance indicators and the methodology adopted in this study. The results are in line with the studies by Degenhart et al (2016) and Di Domenico et al (2017), which reveal public utility companies as the ones that highlight environmental information the most. In this study, this sector had in the second best position regarding technical efficiency, with a score of 44.37%, allowing to infer that this segment has a higher adjustment in ESG variables.…”
Section: General and Sectoral Rankingsupporting
confidence: 90%
“…In a Brazilian context, when analyzing the level of disclosure in the sustainability reports in accordance with the Global Reporting Initiative, in a sample of 93 companies listed in Ibovespa , Di Domenico, Tormem and Mazzioni (2017) found that most companies showed, in a lower way, composite items in the sustainability reports. On the other hand, these authors presented the existence of companies that voluntarily and with quality evidenced the indicators in the reports.…”
Section: Increasing Performance Through Environmental Social and Gove...mentioning
confidence: 99%
“…Ao passo que a Tabela 6 evidencia as pontuações médias de cada setor, destaca-se o segmento de Serviços de Comunicação como o setor com maior eficiência técnica em média (46,86%), conforme os indicadores multidimensionais de desempenho e a metodologia adotados neste estudo. Os resultados vão ao encontro dos trabalhos de Degenhart et al (2016) e de Di Domenico et al (2017), que revelam as empresas do setor de utilidade pública como as que mais evidenciam informações ambientais. Neste estudo, este setor ficou na segunda melhor colocação quanto à eficiência técnica, com uma pontuação de 44,37%, permitindo inferir que esse segmento detém um maior ajuste nas variáveis ESG.…”
Section: Ranking Geral E Setorialunclassified
“…Embora exista uma gama de estudos que têm buscado analisar a divulgação nos relatórios de sustentabilidade com base apenas no volume de informações divulgadas (Deegan & Rankin, 1997;Domenico, Tormem & Mazzioni, 2017;Góis, Santos, Cabral & Pessoa, 2015;Gomes, De Luca, Vasconcelos & Ponte, 2015;Leite Filho, Prates & Guimarães, 2009;Morisue, Ribeiro & Penteado, 2012;Oliveira, De Luca, Ponte & Pontes Júnior, 2009;Santana, Góis, De Luca & Vasconcelos, 2015;Silva, Rocha, Wienhage & Rausch, 2009;Travassos, Costa, Silva & Araújo, 2014), faz-se pertinente considerar a abordagem da qualidade da informação divulgada nos relatórios de sustentabilidade, que tem sido aplicada em número ainda reduzido de estudos sobre divulgação socioambiental (Bouten et al, 2011;Costa & Crisóstomo, 2017;Garcia, Cintra, Ribeiro & Dibbern, 2015;Leszczynska, 2012;Staden & Hooks, 2007;Tannuri & Bellen, 2014).…”
Section: Política De Meio Ambiente No Brasil Abrangência Do Disclosuunclassified